1991
DOI: 10.1103/physrevlett.66.2585
|View full text |Cite
|
Sign up to set email alerts
|

Study of hypernuclei by associated production

Abstract: Data obtained by the associated production of A hypernuclei through the (n + ,K + ) reaction are presented for a wide range of mass numbers. The special features which make this reaction useful are pointed out. The reaction is shown to be an excellent probe of A single-particle states, as demonstrated by the excitation of deeply bound states which are interpreted as the weak coupling of a A to neutronhole states of the core. The A binding energies and ground-state production cross sections for JvBe, 'AC, '&>, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(133 citation statements)
references
References 11 publications
(6 reference statements)
4
128
1
Order By: Relevance
“…3) clearly shows that this state corresponds to the supersymmetric (genuine) hypernuclear state [11][12][13]. The nuclear part has the pronounced 2α cluster structure, and the occupies the p orbital parallel to the symmetry axis.…”
Section: B Discussion On Each Hypernucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…3) clearly shows that this state corresponds to the supersymmetric (genuine) hypernuclear state [11][12][13]. The nuclear part has the pronounced 2α cluster structure, and the occupies the p orbital parallel to the symmetry axis.…”
Section: B Discussion On Each Hypernucleusmentioning
confidence: 99%
“…Owing to experimental developments, some of these phenomena have been observed in light p-shell hypernuclei. As examples, we can refer to the reduction of B(E2) in 7 Li [10] and the identification of the supersymmetric (genuine) hypernuclear state in 9 Be [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…At the larger momentum transfer of the stopped K − work at KEK [9], the same peaks contain contributions from both 0 + and 2 + hypernuclear states. Finally, in the (π + , K + ) reaction, first performed at BNL [10] and later at KEK [2] with better energy resolution, only the 2 + states are expected to contribute.…”
mentioning
confidence: 99%
“…The experimental values [40,41] are also shown for comparison. It is found that the results of set B are closer to the experimental values than those of set A.…”
Section: Resultsmentioning
confidence: 99%
“…Among many strange nuclear systems, the single-Λ hypernucleus is the most investigated one [38]. There exist many experimental data for various single-Λ hypernuclei over almost the whole mass table [38][39][40][41], while there are few experimental data concerning other hypernuclei. Theoretically, the properties of Λ hypernuclei have been investigated based on various models.…”
Section: Introductionmentioning
confidence: 99%